Genetics of primary lateral sclerosis. (2nd November 2020) - Silani, Vincenzo; Corcia, Philippe; Harms, Matthew B.; Rouleau, Guy; Siddique, Teepu; Ticozzi, Nicola
Abstract: With the exception of rare, juvenile-onset, autosomal recessive cases, primary lateral sclerosis (PLS) has long been considered an exclusively sporadic motor neuron disease. However, the identification of PLS cases within pedigrees with familial amyotrophic lateral sclerosis (ALS), together with the clinical and neuropathological overlap with other neurodegenerative disease with strong genetic component such as ALS and hereditary spastic paraparesis (HSP), suggest the existence of a genetic component in PLS as well. Here we will review the genetics of juvenile PLS-like syndromes and the contribution of mutations in ALS and HSP-associated genes to PLS pathogenesis.